Spectrum of Clinical Presentation and Surgical Outcome in Patients with Chronic Subdural Haemorrhage: A Retrospective Study - Malaya Patel; ACHARYA SURYAKANT PATTAJOSHI; Harish Chandra Dhamudia; A Unnikrishnan; J Paul; Prathima Nuthalapati (Journal of Clinical and Diagnostic Research, 2021)
Introduction: Chronic subdural haematomas are one among common neurosurgical emergencies especially affecting elderly male. Usually, presents with subacute Cerebro Vascular Accident (CVA), impaired higher mental function and sometimes with reversible dementia. Rarely, it presents with end stage herniation. Burr Hole Drainage (BHD) is the most popular and worldwide procedure of choice and it successfully address the problem in majority of cases. However, in a small group of patients it needs a wider craniotomy to deal with the subdural membrane which is mainly associated with recurrence of the entity. Aim: To evaluate the comparative incidence of various clinical presentation and analysing the outcome of different treatment modalities in different subgroups of patients with chronic subdural haemorrhage with respect to complication and survivality. Materials and Methods: This retrospective study enrolled data of 100 consecutive patients of subacute (n=30) and chronic subdural haematoma (n=70) who were admitted and undergone neurosurgical management of Veer Surendra Sai Institute of Medical Science and Research (VIMSAR), Burla, Odisha between September 2018 to September 2020. Variables were collected from patient’s records at discharge and analysed with respect to spectrum of clinical presentation and surgical outcome of different treatment modalities and problems associated with it. Results: The mean age group was 57.39 years and headache was the most common clinical presentation in the present study (86%) followed by hemiparasis (74%). BHD was carried out in 94 patients (94%). Primary craniotomy and membrane excision was carried out in 5 patients. Secondary craniotomy was performed in 1 patient after early re-accumulation and clinical deterioration. The outcome was assessed utilising Glasgow outcome scale with total five deaths in the series. Conclusion: Chronic Subdural Haemorrhage (CSDH) a problem of late adulthood (5th to 6th decade) which mostly follows two to three weeks after trauma. It needs proper preoperative assessment and requires timely intervention with skilled nursing care for early recovery. Post-traumatic subacute subdural haematoma in young subject and alcoholics needs special attention during course of their treatment. Bilateral puppilary failure, low Glasgow Coma Scale (GCS) and seizure association are risk factors for poor outcome.